Pathogen‐specific risk of seizure in children with moderate‐to‐severe diarrhoea: Case control study with follow‐up. Issue 8 (18th June 2020) - Afroze, Farzana; Das, Sumon Kumar; Ahmed, Shahnawaz; Sarmin, Monira; Shaly, Nusrat Jahan; Khan, Soroar Hossain; Shahid, Abu Sadat Mohammad Sayeem Bin; Shahrin, Lubaba; Saha, Haimanti; Alam, Tahmina; Faruque, Abu Syed Golam; Shahunja, K. M.; et al.
Abstract: Objective: To determine the pathogen‐specific risk of seizure in under‐five children hospitalised with moderate‐to‐severe diarrhoea (MSD) in rural settings. Method: This was a prospective case–control study with follow‐up, conducted in a sentinel facility of Global Enteric Multicenter Study in Mirzapur, a rural community of Bangladesh between 2007 and 2010. Children aged 0–59 months who presented with MSD and seizure constituted the cases whereas those who did not have seizure comprised the controls. MSD was defined if the episodes were associated with dehydration or dysentery or required hospitalisation with diarrhoea or dysentery. All enrolled children were followed up at home within 50–90 days of enrolment. A total of 64 cases and 128 randomly selected controls formed the analysable dataset. Results: The result of logistic regression analysis after adjusting for potential confounders revealed that shigellosis ( Shigella species, OR = 5.34, 95% CI = 2.37–12.04) particularly S . flexneri (OR = 3.34, 95% CI = 1.48–7.57), S . flexneri 6 (OR = 23.24, 95% CI = 2.79–193.85), S . sonnei (OR = 6.90, 95% CI = 2.34–19.85); norovirus (OR = 6.77, 95% CI = 1.69–27.11), fever (OR = 16.75, 95% CI = 1.81–154.70) and loss of consciousness (OR = 35.25, 95% CI = 1.71–726.20) were the independent risk factors for seizure in MSD children. At enrolment, cases had lower WHZ ( P  = 0.006) compared to their peers, follow‐up anthropometrics showed significant improvement in WHZ ( P  < 0.001) and WAZ ( P  < 0.05), whereas deterioration in HAZ ( P  < 0.001) in both cases and controls. Conclusion: Childhood MSD episodes particularly due to Shigella and norovirus are often associated with seizure. Prompt identification and appropriate management of children with shigellosis may reduce occurrence and adverse consequences of seizure linked with MSD. Abstract : Objectif: Déterminer le risque spécifique de convulsions chez les enfants de moins de cinq ans hospitalisés pour une diarrhée modérée à sévère (DMS) en milieu rural. Méthode: Il s'agissait d'une étude prospective cas‐témoins avec suivi, menée dans un établissement sentinelle de l'Etude Globale Multicentrique Entérique à Mirzapur, une communauté rurale du Bangladesh entre 2007 et 2010. Les enfants âgés de 0 à 59 mois qui se sont présentés avec une DMS et des convulsions constituaient les cas, tandis que ceux qui n'avaient pas des convulsions constituaient les témoins. La DMS a été définie si les épisodes étaient associés à une déshydratation ou à une dysenterie ou nécessitaient une hospitalisation pour diarrhée ou dysenterie. Tous les enfants recrutés ont été suivis à domicile dans les 50 à 90 jours suivant le recrutement. Un total de 64 cas et 128 témoins sélectionnés au hasard ont constitué l'ensemble de données analysables. Résultats: Le résultat de l'analyse de régression logistique après ajustement des facteurs de confusion potentiels a révélé que la shigellose (espèce Shigella, OR = 5, 34 ; IC95%: 2, 37–12, 04) en particulier S. flexneri (OR = 3, 34 ; IC95%: 1, 48–7, 57), S. flexneri 6 (OR = 23, 24 ; IC95%: 2.79–193, 85), S. sonnei (OR = 6, 90 ; IC95%: 2, 34‐19, 85) ; les norovirus (OR = 6, 77 ; IC95%: 1, 69–27, 11), la fièvre (OR = 16, 75 ; IC95%: 1, 81–154, 70) et la perte de conscience (OR = 35, 25 ; IC95%: 1, 71–726, 20) étaient les facteurs de risque indépendants de convulsions chez les enfants souffrant de DMS. Lors du recrutement, les cas avaient un score Z poids pour la taille (ZPT) plus faible ( P  = 0, 006) que leurs pairs, les anthropométries de suivi ont montré une amélioration significative du ZPT ( P  < 0, 001) et du score Z poids pour l'âge ( P  < 0, 05); tandis que le score Z taille pour l'âge ( p  < 0, 001) s'est détérioré chez cas et chez les témoins. Conclusion: Les épisodes de DMS de l'enfance, notamment due à Shigella et aux norovirus, sont souvent associés à des convulsions. L'identification rapide et la prise en charge appropriée des enfants atteints de shigellose peuvent réduire la survenue et les conséquences négatives des crises liées aux DMS.